Peran Pemerintah dalam Pengembangan Ekonomi Hinterland di Kabupaten Rokan Hulu Melalui Pemanfaatan Sumber Daya Alam Sawit - Ahmad Khusaini; Lutfia Bamatraf; Belia Afifah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This study aims to analyze the role of government in the development of the hinterland economy in Rokan Hulu Regency through the utilization of natural resources, focusing on a case study of oil palm plantations in accelerating regional economic growth. The method used in this study is a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) to evaluate the strengths, weaknesses, opportunities, and threats associated with the development of the oil palm plantation sector in the district. This study uses a qualitative approach by collecting data through literature studies, interviews with relevant stakeholders, and analysis of existing policies. The data collected will be analyzed descriptively and interpreted to gain a deep understanding of the role of government in the development of the hinterland economy in Rokan Hulu Regency. From the results of the study using SWOT analysis of the role of government in developing the hinterland economy in Rokan Hulu Regency through natural resources (oil palm industry) are the strengths and weaknesses of internal factors of 1.82 and external factors of 0.27. In this effort, there needs to be implementation of appropriate policies between all related parties so as to help achieve sustainable economic growth, create jobs, improve community welfare, andmaintain environmental sustainability in Rokan Hulu Regency.